Spontaneous Lower Gastrointestinal Bleeding Following Casirivimab/Imdevimab Treatment for COVID-19 Infection: A Case Presentation and Short Literature Review - KM, Ajmera; Heather, Wilkinson (Archives of Clinical and Biomedical Research, 2021)
Coronavirus disease 2019 (Covid-19), which is caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV)-2, has been a global pandemic since January 2020. The scale and rate of efforts to develop vaccines and therapies for Covid-19 are unprecedented. For mild to moderate disease, two recombinant neutralizing monoclonal antibodies (mAb) therapies, bamlanivimab (LYCoV555) and casirivimab/imdevimab (REGNCOV2), have been approved by the United States Food and Drug Administration to be administered within 10 days of symptom onset. The efficacy and safety of mAbs are well documented. In this report, we present the first case of life-threatening lower gastrointestinal bleeding potentially related to REGNCOV2 treatment.